STRATEGI PENGEMBANGAN PULAU GEBE PASCA PENAMBANGAN NIKEL YANG BERKELANJUTAN - Mardi Wibowo (Jurnal Rekayasa Lingkungan)
Since 1977 until 2005, PT. ANTAM has been exploited nickel ore resources at Gebe Island – Center of Halmahera District – North Maluku Province. Mining activity not only gives economically advantages, but also causes degradation of environment quality especially land quality. Therefore, it needs evaluation activity for land quality changing at Gebe Island after the mining activity (postmining). For handling Gebe Island after mining activity needs identification of the problems, potential and obstacles as the basic for arranging development strategy of Gebe Island. This research used Focused Group Discussion (FGD) method, desk study and field survey. Base on this research the important think has to be done, are : (a) to make or open new market at surround Gebe Island; (b) development Gebe Island has be base on locally resources and export oriented; (c ) needinvestor as prime mover in Gebe Island; (d) optimize of PT ANTAM’s asset; (e) increase institution coordination and program integration.Key words : sustainable development, post mining